Configurações subjetivas de alunos com deficiência visual sobre processos de escolarização no ensino médio - Sales, Edinaldo Bomfim (Universidade Federal de São Carlos, 2019)
Valuing the search for the materialization of the right to inclusive education and other cultural goods, the present study focuses on the developmental conditions of the schooling of students with visual impairment in high school, since historically they are people who have endured harmful representations of disability or extraordinariness; where exclusion, prejudice and disinformation about rights still prevail. We produced a research with visually impaired students from a municipality in the interior of the State of Pará, with a focus on the theory of subjectivity and its qualitative epistemology. This is a multiple case study using the constructive-interpretive method. The participants were three visually impaired students from high school and the main objective of the study was to understand the processes of subjectivation made up of blind students with low vision about the processes of schooling in high school. The production of information with these participants is justified by the fact that they are subjects in the condition of disability who experience or experienced different school realities, being individuals with the capacity to express themselves in depth about the research topic. Seeking to achieve an open dialogic communication with the participants, we promoted several meetings to build a social research scene; from there we begin to use the instruments individually with each of them, to produce the information; in which, first, we used a questionnaire, followed by an interview script, followed by an oral sentence completion and we ended with a conversational dynamic. During the dialogues, the participants brought narratives and statements about the factual situations of their experiences in the common room, and the implications of the condition of disability, which always coincided with the condition of individuals, became apparent. Expressions emerged that pointed to a bipolarization of "worlds" of people with and without disabilities, which made it possible to understand that the challenge of school inclusion would be the capacity for interrelationship, which must be assumed by all. We identified some experiences also surrounded by the issue of disability, the transfer of the classroom due to the normative adequacy of the amount of student, situations experienced in a common classroom marked by the forgetfulness or treatment of invisibility by the teachers, but also the support of the colleagues without disabilities, who collaborated in the development of activities. Uniquely, the three cases evidenced how the passage through secondary education seemed important to impact subjective configurations of students with visual impairment, reducing the senses of loss, allowing access to knowledge, personal development, and progression in the schooling process. The information shows that in the context of the greatest barriers, it is that the processes of subjectivation are more mobilized by impelling and teaching individuals to face them as subjects that started to self-affirm, decentralized from a homogeneous school social condition. It is hoped that the design of a multiple case study using the constructive-interpretive method has contributed to show the singularities of the subjective configurations of blind individuals with low vision about their schooling in high school.
Keywords: Deficiência visual; Escolarização; Ensino médio; Subjetividade; Visual impairment; Schooling; High school; Subjectivity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO